Application of Differential Evolution in the Solution of Stiff System of Ordinary Differential Equations - Wusu, Ashiribo Senapon; Olabanjo, Olusola; Aribisala, Benjamin (Transactions on Engineering and Computing Sciences, 2020)
In recent times, the adaptation of evolutionary optimization algorithms for obtaining optimal solutions of many classical problems is gaining popularity. In this paper, optimal approximate solutions of initial--valued stiff system of first--order Ordinary Differential Equation (ODE) are obtained by converting the ODE into constrained optimization problem. The later is then solve via differential evolution algorithm. To illustrate the efficiency of the proposed approach, two numerical examples were considered. This approach showed significant improvement on the accuracy of the results produced compared with existing methods discussed in literature.